Analisis Penggunaan Artificial Intelligence (AI) Pendidikan dalam Mendukung Guru dan Siswa - Lauw Acep; Abhinaya Cadudasa; Pheng Khiu Danawe; Tuty Tuty (Dhammavicaya : Jurnal Pengkajian Dhamma, 2025)
The development of Artificial Intelligence (AI) has brought significant changes to the world of education, particularly in supporting teachers' work and student learning. This research examines the role of AI in helping teachers develop interactive and relevant teaching materials, facilitating student self-directed learning, and identifying challenges and ethical issues arising from its implementation. The research method used in this study is a literature review combined with case analysis of the use of AI-based learning platforms such as ChatGPT and other adaptive systems. The results show that AI offers significant potential for improving the efficiency of teaching material development, supporting personalized learning tailored to individual student needs, and enhancing student engagement through interactivity and real-time feedback. As a differentiated approach, this research also integrates Buddhist perspectives, particularly the concepts of sati (mindfulness) and paññā (wisdom) found in the Dhammapada, as well as ethical principles of learning from the Sigalovada Sutta. This perspective emphasizes the importance of balancing technological innovation with the development of wise and responsible character. This research identified several important challenges, such as disparities in access to digital technology across regions, privacy and data security concerns, potential bias in AI algorithms, and concerns about technological dependency that could diminish students' critical and reflective thinking skills. Therefore, while AI has transformative potential to support learning in the digital age, its implementation must be carried out ethically and wisely. A balanced approach between technological innovation and humanitarian values as taught in Buddhist teachings is key to creating an inclusive, equitable, and sustainable education ecosystem.